Properties of Fuzzy Resolving Set (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a fuzzy graph , for a subset  of , the representation of  with respect to  in terms of strength of connectedness of vertices are distinct then  is called the fuzzy resolving set of . In this article, we discuss the properties of fuzzy resolving set and fuzzy resolving number. And also proved some theorems and properties of fuzzy resolving number in fuzzy cyclic and fuzzy labeling graphs.